PERUBAHAN SIFAT MEKANIK BAJA KONSTRUKSI JIS G4051 S17C SETELAH DILAKUKAN HARDENING DAN TEMPERING - Media Nofri (Bina Teknika, 2015)
Material JIS G 4051 S 17 C including low carbon steel with alloy composition 0:15% C, 0.157% Si, 1.2% Mn, 0.01% P, of 0.02% S. Low carbon steels are widely applied for construction machinery. This study aimed to analyze the effects of the process of hardening and tempering on material hardness, impack and metallografi. Results of this research show the value of Brinell hardness will increase the hardening process with temperatures of 900 C, holding time 15 minutes and the coolant medium is water. Brinell hardness is HB 364.22, is due to the structure of ferrite and pearlite transformed to martensite. Impack results increased in the process of tempering with temperature 500 C, holding time 15 minutes are cooled with air. Impack toughness value of 0.447 Joule / mm2, is because the value of tenacity to grow up and hardness decreased in the coarse grain structure.